Effects of Pilates on Body Posture: ASystematic Review - Li, Fangyi; Omar Dev, Roxana Dev; Soh, Kim Geok; Wang, Chen; Yuan, Yubin (Elsevier, 2024)
Objective: To perform a systematic review of the effects of Pilates on common body postures. Data sources: Web of Science, PubMed, Scopus, Science Direct, Springer Link, and CNKI. The search year is set from January 1, 2019, to November 15, 2023. Study Selection: Quasi-experimental studies, randomized controlled trials, randomized clinical trials, and nonrandomized controlled trials investigating the effects of Pilates on body posture. Data Extraction: The Physiotherapy Evidence Database scale was used to evaluate the quality of studies that met the inclusion requirements. Studies were independently assessed by 2 reviewers who read through the full text and labeled as “low quality,” “moderate quality,” “good quality,” and “excellence quality.” Disagreements were resolved by the third reviewer. The Cochrane Risk of Bias (RoB 2.0) tool was used to assess the risk of bias for each study. Data Synthesis: Of the 492 studies screened, 13 met the inclusion criteria involving a total of 783 trial participants. Six studies (46%) were of high quality or above, with main limitation related to the internal validity of the study design. The research outcomes focused primarily on effects of Pilates on body posture; cervical, thoracic, and lumbar spine; and followed by quality of life and pain. Conclusions: The findings of this systematic review provided valuable evidence for the role of Pilates in improving body posture problems. Pilates is a boon to patients suffering from postural disorders, and it is suggested that Pilates can be widely used as a complementary therapy. Nonetheless, more detailed studies are necessary in the future.